A kind of high-efficiency flame-retardant polyurethane and preparation method thereof

By adding microencapsulated flame retardant and modified expandable graphite to the polyurethane material, the problems of flammability of polyurethane materials and low efficiency of traditional flame retardant are solved, and efficient and stable flame retardant performance and material performance uniformity are achieved.

CN118580458BActive Publication Date: 2025-04-18CHINA CONSTR EIGHTH ENG GRP (SHANDONG) NEW MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410625249.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-04-18
Estimated Expiration
2044-05-20

AI Technical Summary

Technical Problem

Polyurethane materials cause fire accidents due to flammability, and traditional flame retardant additives are large and the flame retardant efficiency is low, making it difficult to maintain the flame retardant performance of the material.

Method used

By adding microencapsulated flame retardant and modified expandable graphite, the modified expandable graphite is prepared by homogeneous emulsification process of materials such as urea phosphate, urea, dispersant, emulsifier, etc. to form uniformly dispersed modified expandable graphite, and synergistically exerts the flame retardant effect.

Benefits of technology

It significantly improves the flame retardant performance of polyurethane materials, avoids the migration of flame retardant, enhances the mechanical properties and performance uniformity of the material, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004848392460000041
    Figure BDA0004848392460000041
  • Figure BDA0004848392460000111
    Figure BDA0004848392460000111
  • Figure BDA0004848392460000121
    Figure BDA0004848392460000121
Patent Text Reader

Abstract

The present application discloses a kind of high-efficiency flame-retardant polyurethane and its preparation method, and belongs to the technical field of flame-retardant polyurethane materials. The high-efficiency flame-retardant polyurethane comprises, by weight, 20-25 parts of microencapsulated dimethyl methylphosphonate, 100-130 parts of modified expandable graphite, 50-70 parts of polyether polyols, 50-80 parts of polyester polyols, 10-13 parts of chain extenders, 130-150 parts of diisocyanates, 1-2 parts of foaming agents, 0.5-1 parts of catalysts, 2-3 parts of surfactants and 1-2 parts of water. By adding microencapsulated flame retardants and modified expandable graphite to the high-efficiency flame-retardant polyurethane, the polyurethane material can be flame-retardantly modified to solve the fire safety problem that the polyurethane material may bring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a highly efficient flame-retardant polyurethane and a preparation method thereof, belonging to the technical field of flame-retardant polyurethane materials. Background Art

[0002] Polyurethane materials are widely used in production and life due to their unique structure and excellent performance. Polyurethane materials are generally used as filling and filling materials to shield and protect wires and cables, and to increase the service life of wires and cables; they can also be used as filling and repairing materials for rock cracks in coal and mines. They have high mechanical strength, environmental tolerance, no environmental pollution, and a non-toxic matrix after curing, and are suitable for underground casting.

[0003] Liquid polyurethane foam can be used as a filling material. When used, the two components are mixed to foam and expand, and then sprayed into the cracks. After solidification, the coal and rock are bonded together to achieve the purpose of reinforcement. At the same time, due to the closed-cell structure inside the rigid polyurethane material and the very low thermal conductivity of the high molecular polymer itself, polyurethane materials can also be generally used as exterior wall insulation materials for house buildings.

[0004] The polyurethane matrix itself may cause polyurethane fire accidents due to its flammability, and release a large amount of toxic gases, such as carbon monoxide (CO) and hydrogen cyanide (HCN). Therefore, it is necessary to perform flame retardant treatment on polyurethane materials. At present, adding dimethyl methylphosphonate as a flame retardant to polyurethane materials has been industrially applied, but since dimethyl methylphosphonate is in liquid phase, it will migrate out of the matrix with part of dimethyl methylphosphonate as the polyurethane material is used, so it is difficult to maintain the flame retardant properties of the polyurethane material. Summary of the invention

[0005] In order to solve the above problems, a high-efficiency flame-retardant polyurethane and a preparation method thereof are provided. By adding microencapsulated flame retardants and modified expandable graphite to the high-efficiency flame-retardant polyurethane, the polyurethane material can be flame-retardantly modified to solve the fire safety problems that may be caused by the polyurethane material.

[0006] According to one aspect of the present application, a high-efficiency flame-retardant polyurethane is provided, which includes, by weight: 20-25 parts of microencapsulated dimethyl methylphosphonate, 100-130 parts of modified expandable graphite, 50-70 parts of polyether polyols, 50-80 parts of polyester polyols, 10-13 parts of chain extenders, 130-150 parts of diisocyanates, 1-2 parts of foaming agents, 0.5-1 parts of catalysts, 2-3 parts of surfactants and 1-2 parts of water.

[0007] The present application uses microencapsulated dimethyl methylphosphonate as a flame retardant, which can improve the stability of the flame retardant in the matrix, thereby avoiding the migration of dimethyl methylphosphonate and always maintaining the flame retardant properties of the polyurethane material. In addition, the microencapsulated dimethyl methylphosphonate and the modified expandable graphite cooperate with each other and can exert the best flame retardant effect under the above ratio. At the same time, the two can be evenly dispersed in the matrix, improving the performance uniformity of the polyurethane material.

[0008] Optionally, the microencapsulated dimethyl methylphosphonate includes a capsule core, a first capsule wall and a second capsule wall from the inside to the outside, the capsule core is dimethyl methylphosphonate, the first capsule wall is polyurethane, and the second capsule wall is melamine formaldehyde copolymer.

[0009] Compared with the case where the first capsule wall is made of styrene divinylbenzene copolymer, the first capsule wall made of polyurethane has a stronger bonding force with the second capsule wall made of melamine formaldehyde copolymer, which can improve the stability between the first capsule wall and the second capsule wall, and avoid delamination between the two, so as to play a long-term role in protecting and fixing the capsule core. In addition, the first capsule wall is made of polyurethane, which can improve the compatibility of microencapsulated dimethyl methylphosphonate with the matrix, promote the uniform dispersion of microencapsulated dimethyl methylphosphonate in the matrix, not only making dimethyl methylphosphonate stably exist in the matrix, but also achieving a uniform flame retardant effect.

[0010] In addition, the second capsule wall is a melamine formaldehyde copolymer, which also has flame retardant properties, thereby increasing the flame retardant effect of the microencapsulated dimethyl methylphosphonate.

[0011] Optionally, the preparation method of the microencapsulated dimethyl methylphosphonate is:

[0012] S1: Disperse dimethyl methylphosphonate in water, stir at 25-60°C for 2-3h, then add emulsifier to start emulsification for 10-120min, finally add diisocyanate dropwise, and react at a constant temperature of 10-80°C for 2-24h to obtain an intermediate solution;

[0013] S2: Mix melamine, formaldehyde aqueous solution and deionized water in a weight ratio of 1:(2-3):(8-10), adjust the pH to 8-9 with triethanolamine, then stir at 50-80° C. to form a transparent liquid, and then add a certain amount of distilled water to obtain a melamine-formaldehyde prepolymer solution;

[0014] S3: adding melamine-formaldehyde prepolymer solution to the intermediate solution, reacting at 60-80° C. for 2-3 hours, filtering, washing and drying to obtain microencapsulated dimethyl methylphosphonate.

[0015] In step S1, diisocyanate and water react to form polyurethane, which tightly coats dimethyl methylphosphonate to obtain an intermediate solution containing a large number of solid small particles. Then, in step S3, melamine-formaldehyde prepolymer is polymerized to form melamine-formaldehyde copolymer, thereby forming a second capsule wall for coating again. In this process, the melamine-formaldehyde copolymer can be tightly combined with the polyurethane capsule wall, and the contact force between the first capsule wall and the second capsule wall is enhanced.

[0016] Optionally, in step S1, the weight ratio of the diisocyanate to dimethyl methylphosphonate is at least one of 4:1, 6:1, and 8:1, preferably 4:1, and the weight ratio of the diisocyanate to water is 1:1-2.

[0017] Optionally, in step S3, the weight ratio of melamine to dimethyl methylphosphonate is (0.5-0.7):1.

[0018] Optionally, the emulsifier is selected from Span 80 or Tween 80.

[0019] Optionally, the chain extender is prepared from N,N-bis(hydroxymethyl)-urea, and the specific preparation method is:

[0020] S1: dissolving N,N-bis(hydroxymethyl)urea in a solvent, adding formic acid and formaldehyde at room temperature, wherein the molar ratio of N,N-bis(hydroxymethyl)urea, formaldehyde and formaldehyde is 1:1:1, then heating to 70-80°C for reaction for 9-12h, then adjusting the pH to 10-11, extracting and drying to obtain an intermediate;

[0021] S2: dissolving the intermediate in ethanol, adding a small amount of citric acid and disodium ethylenediaminetetraacetate, heating to 60-70°C, adding hydrogen peroxide, wherein the molar ratio of hydrogen peroxide to N,N-bis(hydroxymethyl)-urea is 1:1, reacting for at least 4 hours, distilling and purifying to obtain the chain extender.

[0022] The chain extender can extend the molecular chain length of the polyurethane material, thereby adjusting the crosslinking degree of the polyurethane material to adjust the mechanical properties, foaming uniformity and thermal insulation of the polyurethane material. The present application further adopts a homemade chain extender, which not only has two hydroxyl groups that can participate in the reaction of the polyurethane, but also has two amine oxide groups in the chain extender through the reaction of steps S1 and S2. First, it can enhance the flame retardant effect of the polyurethane molecular chain; second, it contains the N element, which improves the compatibility of microencapsulated dimethyl methylphosphonate and promotes the uniform dispersion of microencapsulated dimethyl methylphosphonate; third, it can suppress the smoke emission of the material combustion and reduce the generation of combustion gas.

[0023] The other two amine oxide groups are both connected to the carbon-oxygen double bond. It has been verified that the carbon-oxygen double bond can promote the above-mentioned effect of the amine oxide, and the closer the carbon-oxygen double bond is to the amine oxide group, the more obvious the promotion effect. Therefore, the carbon-oxygen double bond contained in the chain extender in this application is directly connected to the two amine oxide groups, which can optimize the above-mentioned effect of the amine oxide.

[0024]

[0025] Optionally, the added amount of citric acid accounts for 2% of the weight of N,N-bis(hydroxymethyl)-urea, and the added amount of disodium ethylenediaminetetraacetate accounts for 5% of the weight of N,N-bis(hydroxymethyl)-urea.

[0026] Preferably, the solvent is a mixed solvent of water and ethanol in a weight ratio of 2-3:1.

[0027] Optionally, the diisocyanate is selected from at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and hexamethylene diisocyanate;

[0028] The polyether polyol is selected from polyether triol or polyether tetraol, and the hydroxyl value of the polyether polyol is 350-650 mgKOH / g;

[0029] The polyester polyol is selected from at least one of polycaprolactone polyol, polycarbonate polyol and polyacrylate polyol, and the hydroxyl value of the polyester polyol is 350-650 mg KOH / g.

[0030] Optionally, the foaming agent is selected from at least one of n-pentane, n-hexane and cyclohexane;

[0031] The catalyst is selected from at least one of dibutyltin dilaurate, bis(dimethylaminoethyl) ether, N,N-dimethylcyclohexylamine, and 1,4-dimethylpiperazine;

[0032] The surfactant is selected from at least one of benzyl silicone oil, diethyl silicone oil, methyl hydrogen silicone oil and methyl vinyl silicone oil.

[0033] Optionally, the modified expandable graphite has a particle size of 0.5-10 μm and an expansion coefficient of 250-290 ml / g.

[0034] Optionally, the modification method of the modified expandable graphite is:

[0035] S10: Phosphoric acid and urea are mixed in a molar ratio of (0.5-1):1, and reacted at 80-100° C. to obtain urea phosphate, expandable graphite, a dispersant, and an emulsifier are added to the urea phosphate, and the mixture is stirred at 80-100° C. to obtain a colloid, the colloid is emulsified in an emulsifier, and then transferred to a polymerization furnace to polymerize at 150-240° C. and 10-45 KPa to obtain a composite material, and the composite material is cooled, dried, and crushed to obtain intermediate microspheres A;

[0036] S20: mixing the intermediate microsphere A and N-aminoethyl-3-aminopropyltriethoxysilane in a solvent and heating to 80° C. to react, filtering, washing, and drying to obtain the intermediate microsphere B with amino groups;

[0037] S30: reacting monomer A, formaldehyde compound and intermediate microsphere B under an acid catalyst, filtering, washing and drying to obtain intermediate microsphere C, wherein monomer A is selected from at least one of p-acetoxystyrene, diacetone acrylamide and benzylidene acetone;

[0038] S40: placing the intermediate microspheres C in a 3-mercaptopropyltriethoxysilane solution, reacting under the initiator, filtering, washing and drying to obtain modified expandable graphite.

[0039] In the preparation method, the intermediate microspheres A obtained in step S10 contain ammonium polyphosphate between the graphite layers, which can improve the adhesion between the expandable graphite, thereby improving the flame retardant effect of the expandable graphite. In step S20, N-aminoethyl-3-aminopropyltriethoxysilane is used to react with the intermediate microspheres A to obtain the intermediate microspheres B. Firstly, the compatibility of the intermediate microspheres B with the polyurethane substrate can be improved, so that the expandable graphite and the matrix form a uniform and stable state, and the sedimentation and agglomeration of the expandable graphite are avoided, thereby improving the performance uniformity of the polymer matrix and the flame retardant uniformity of the expandable graphite to the matrix; secondly, the intermediate microspheres B contain NH and NH2 groups, which can not only absorb toxic gases and reduce the combustion hazard, but also participate in the reaction of isocyanate to form polyurethane, form a chemical bond with the polyurethane matrix, and improve the bonding force between the expandable graphite and the matrix, so that the flame retardant carbon layer is tightly combined with the matrix, and the protection of the matrix is ​​improved. In step S30, the intermediate microspheres C can also be obtained by reacting with the monomer A formaldehyde compound. Due to the presence of monomer A, the intermediate microspheres C prepared in step S30 can introduce functional groups such as benzene rings, carbonyl groups, ester groups, and amino groups into expandable graphite. The benzene rings can strengthen the matrix and improve the mechanical properties of the matrix. The carbonyl groups and ester groups can further increase the compatibility with the polyurethane matrix. The amino groups can further increase the number of binding sites with the polyurethane matrix and increase the adsorption of toxic gases. Since the monomers A in step S30 all contain double bonds, 3-mercaptopropyltriethoxysilane is used in step S40 to react with the double bonds to obtain silane-terminated modified expandable graphite, which can further improve the dispersibility and stability of expandable graphite in the matrix, and improve the adhesion between expandable graphites, so that the strength and density of the flame-retardant carbon layer are improved, so that the toxic gases are adsorbed and effectively blocked, reducing the harm of toxic gases to the human body.

[0040] The intermediate microspheres A obtained in the above step S10 allow ammonium polyphosphate to be contained between the graphite layers, which not only improves the bonding force between the expandable graphites and increases the strength of the flame-retardant carbon layer, but also can simultaneously improve the flame-retardant properties of the expandable graphite because the ammonium polyphosphate itself is also flame-retardant; in steps S20-S40, the surface of the expandable graphite contains modified molecular chains, which can firstly achieve the adsorption of toxic gases; secondly, improve the compatibility of the expandable graphite with the matrix, improve the dispersion uniformity of the expandable graphite, avoid the sedimentation or agglomeration of the expandable graphite, and also improve the performance uniformity of the polyurethane composite material; thirdly, it can be chemically combined with the polyurethane matrix, so that the flame-retardant carbon layer is tightly combined with the matrix, and the toxic gas is effectively blocked, and the compactness, uniformity and mechanical strength of the flame-retardant carbon layer can be improved, and it can resist the impact of open flames or heat convection.

[0041] The modified expandable graphite prepared by the above method can be more evenly dispersed, so when used as a flame retardant, the usage amount can be effectively reduced, thereby reducing the density of the material, and also avoiding the problem of falling off due to excessive mass when used as a building exterior wall.

[0042] Optionally, in step S10, the expandable graphite accounts for 5-30% of the weight of the urea phosphate, the dispersant accounts for 0.5% of the weight of the urea phosphate, and the emulsifier accounts for 0.5% of the weight of the urea phosphate.

[0043] In the above step S10, the intermediate microspheres A are obtained by a homogenizing emulsification process, which can solve the problem of difficult dispersion of expandable graphite and ammonium polyphosphate emulsion. Under the high shear force of the homogenizing emulsifier, many small droplets are formed inside the emulsion, and the microstructure of the expandable graphite particles wrapped by the ammonium polyphosphate emulsion is realized. During the polymerization process, the expandable graphite particles can be evenly dispersed, thereby improving the modification effect of ammonium polyphosphate on the expandable graphite.

[0044] Since the expandable graphite contains ammonium polyphosphate between the layers, the ammonium polyphosphate decomposes into ammonia and polyphosphoric acid when heated. The ammonia can dilute the oxygen concentration, and the polyphosphoric acid has good thermal stability. The expandable graphite expands rapidly after heating, which can effectively isolate the oxygen required for combustion. At the same time, the interior has a porous property, which absorbs the combustion smoke and reduces the possibility of re-combustion. It can also effectively isolate the combustion oxygen and improve the flame retardant properties of the material.

[0045] Optionally, in step S20, the weight ratio of the intermediate microsphere A to N-aminoethyl-3-aminopropyltriethoxysilane is 1:(1-2);

[0046] The heating reaction time in step S20 is 8-10 hours.

[0047] The surface of expandable graphite contains a large number of hydroxyl groups. Through the reaction of N-aminoethyl-3-aminopropyltriethoxysilane and intermediate microspheres A, N-aminoethyl-3-aminopropyltriethoxysilane can react with the hydroxyl groups to achieve the grafting of N-aminoethyl-3-aminopropyltriethoxysilane on the surface of expandable graphite. The above reaction conditions can increase the reaction rate of N-aminoethyl-3-aminopropyltriethoxysilane and intermediate microspheres A, and increase the amount of N-aminoethyl-3-aminopropyltriethoxysilane on the surface of expandable graphite, thereby synergistically improving the flame retardant, reinforcing, toxic gas adsorption and compactness improvement effects of the modified expandable graphite on the matrix.

[0048] If the weight of N-aminoethyl-3-aminopropyltriethoxysilane is too much, the amount of N-aminoethyl-3-aminopropyltriethoxysilane on the surface of expandable graphite increases. Combined with the reactions of subsequent steps S30 and S40, too many molecular chains are introduced into the surface of expandable graphite, which weakens the bonding force between expandable graphites. The flame-retardant carbon layer still has cracks, and the flame-retardant and toxic gas barrier effects are reduced. If the weight of N-aminoethyl-3-aminopropyltriethoxysilane is too little, the modification effect of expandable graphite is reduced, and the flame-retardant, reinforcing, toxic gas adsorption and density improvement effects of the matrix are all reduced.

[0049] Optionally, in step S30, the weight ratio of monomer A, formaldehyde compound and intermediate microsphere B is (1-2): (1-3): 1;

[0050] The reaction temperature of step S30 is 50-60°C and the reaction time is 8-12h;

[0051] Preferably, the acidic catalyst is selected from at least one of nicotinic acid, sulfuric acid, acetic acid and nitric acid.

[0052] The above-mentioned weight ratio and reaction conditions can improve the reaction efficiency of monomer A, formaldehyde compounds and intermediate microspheres B, and promote monomer A and formaldehyde compounds to react with the amino groups in N-aminoethyl-3-aminopropyltriethoxysilane, thereby introducing new functional groups, increasing the number of functional groups in the intermediate microspheres B, and further synergistically improving the flame retardant and reinforcing effects of expandable graphite on the matrix.

[0053] Optionally, the monomer A is selected from diacetone acrylamide and benzylidene acetone;

[0054] The formaldehyde compound is selected from trioxymethylene and / or polyformaldehyde.

[0055] Optionally, the molar ratio of diacetone acrylamide to benzyl acetone is 3:1.

[0056] It has been verified that when a single type of monomer A reacts with formaldehyde compounds and intermediate microspheres B, after monomer A is connected to intermediate microspheres B, it will hinder the subsequent reaction of monomer A, thereby reducing the reaction participation rate of monomer A, resulting in a part of the molecular chain on the surface of the intermediate microsphere C being terminated with monomer A, and the other part being terminated with N-aminoethyl-3-aminopropyltriethoxysilane. The selection of diacetone acrylamide and benzylidene acetone with a molar ratio of 3:1 as monomer A can increase the reaction participation rate of monomer A, so that the reaction rate of N-aminoethyl-3-aminopropyltriethoxysilane on the surface of intermediate microspheres B and monomer A is greater than 98%. In addition, two functional groups with amino groups and benzene rings can be simultaneously given to intermediate microspheres C, thereby enhancing the mechanical strength of the matrix and the chemical bonding with the matrix, thereby achieving a close and uniform connection between the modified expandable graphite and the matrix.

[0057] Optionally, in step S40, the weight ratio of the intermediate microspheres C to 3-mercaptopropyltriethoxysilane is 1:(5-10);

[0058] Preferably, the initiator in step S40 is a free radical initiator, the reaction temperature is 60-70° C., and the reaction time is at least 5 hours.

[0059] Preferably, the free radical initiator is AIBN.

[0060] The surface of the intermediate microsphere C is capped with monomer A, so that the surface of the intermediate microsphere contains a large number of double bonds. In step S40, the double bonds react with the thiol group to reintroduce the siloxane molecular chain into the modified expandable graphite. At this time, both ends of the molecular chain on the surface of the modified expandable graphite are siloxane molecular chains, which can improve the dispersibility and stability of the modified expandable graphite in the matrix. Under the premise of stable dispersion, the reaction uniformity of the amino group in the molecular chain on the surface of the modified expandable graphite and the isocyanate can be improved, thereby improving the uniformity of chemical bonding with the matrix, and the modified expandable graphite is uniformly embedded in the matrix. In a high temperature environment, the modified expandable graphite has a strong bonding force with the matrix, and the toxic matrix produced by the matrix is ​​adsorbed and blocked at the first time, thereby improving the safety of the polyurethane thermal insulation material.

[0061] According to another aspect of the present application, a method for preparing the high-efficiency flame-retardant polyurethane described in any one of the above items is provided, comprising the following steps:

[0062] (1) mixing microencapsulated dimethyl methylphosphonate, modified expandable graphite, polyether polyol, polyester polyol, foaming agent, catalyst, surfactant and water to obtain a mixed solution;

[0063] (2) adding a chain extender and diisocyanate to the mixed solution, stirring and pouring the mixture into a mold for foaming and aging to obtain a highly efficient flame-retardant polyurethane material.

[0064] Optionally, the foaming and maturing temperature is 65-80°C.

[0065] The beneficial effects of this application include but are not limited to:

[0066] 1. The high-efficiency flame-retardant polyurethane of the present application can play a flame-retardant role in both the gas phase and the condensed phase. During combustion, it can generate gas phase products that can be decomposed to generate phosphorus oxygen free radicals, thereby capturing the free radicals required for the combustion reaction; it can generate acid substances such as metaphosphoric acid, pyrophosphoric acid, and polymetaphosphoric acid in the condensed phase, dehydrate and carbonize the polymer, and avoid the generation of combustible gases. At the same time, a coke layer is formed on the surface of the combustion material to isolate the combustion environment.

[0067] 2. The high-efficiency flame-retardant polyurethane of the present application is prepared with microencapsulated dimethyl methylphosphonate as the main flame retardant and modified expandable graphite as the auxiliary flame retardant. Its flame retardant effect is greatly improved, which effectively solves the problems of large addition amount and low flame retardant efficiency of traditional additive flame retardants, and avoids affecting the mechanical properties of the material.

[0068] 3. The high-efficiency flame-retardant polyurethane of the present application, microencapsulated dimethyl methylphosphonate solves the migration problem of dimethyl methylphosphonate during use, and improves the compatibility with the matrix and the bonding strength with the second capsule wall, avoiding delamination of the first capsule wall and the second capsule wall, doubly improving the service life of the flame-retardant polyurethane material, and is a green, environmentally friendly and efficient halogen-free flame-retardant building insulation material that complies with the dual carbon strategy.

[0069] 4. The highly efficient flame-retardant polyurethane and modified expandable graphite of the present application release non-combustible gas during the thermal expansion process, diluting the oxygen concentration and combustible gas concentration in the atmosphere, and forming a worm-like carbon layer, which increases the combustible gas release path and achieves a flame retardant effect.

[0070] 5. The high-efficiency flame-retardant polyurethane of the present application coordinately regulates the flame-retardant properties of the polyurethane material by controlling the ratio of microencapsulated dimethyl methylphosphonate and modified expandable graphite. The operation is flexible and convenient, and has broad industrial application prospects. DETAILED DESCRIPTION

[0071] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0072] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0073] Unless otherwise specified, the methods used in the embodiments of the present application are conventional methods in the prior art.

[0074] Example 1

[0075] This embodiment relates to the preparation of modified expandable graphite, which comprises the following steps:

[0076] S10: Phosphoric acid and urea are mixed in a molar ratio of (0.5-1):1, and reacted at 80-100° C. to obtain urea phosphate, expandable graphite, a dispersant, and an emulsifier are added to the urea phosphate, and the mixture is stirred at 80-100° C. to obtain a colloid, the colloid is emulsified in an emulsifier, and then transferred to a polymerization furnace to polymerize at 150-240° C. and 10-45 KPa to obtain a composite material, and the composite material is cooled, dried, and crushed to obtain intermediate microspheres A;

[0077] S20: mixing the intermediate microsphere A and N-aminoethyl-3-aminopropyltriethoxysilane in a solvent and heating to 80° C. to react, filtering, washing, and drying to obtain the intermediate microsphere B with amino groups;

[0078] S30: reacting monomer A, formaldehyde compound and intermediate microsphere B under an acid catalyst, filtering, washing and drying to obtain intermediate microsphere C, wherein monomer A is selected from at least one of p-acetoxystyrene, diacetone acrylamide and benzylidene acetone;

[0079] S40: placing the intermediate microspheres C in a 3-mercaptopropyltriethoxysilane solution, reacting under the initiator, filtering, washing and drying to obtain modified expandable graphite.

[0080] Modified expandable graphites 1#-8# and comparative modified expandable graphites D1#-D4# were prepared according to the above preparation steps, as follows:

[0081] Modified expandable graphite 1#

[0082] The preparation method of the modified expandable graphite 1# comprises the following steps:

[0083] S10: Phosphoric acid and urea are mixed at a molar ratio of 0.5:1, and reacted at 100°C to obtain urea phosphate, expandable graphite, dispersant, and emulsifier are added to the urea phosphate, wherein the expandable graphite accounts for 5% of the weight of the urea phosphate, the dispersant accounts for 0.5% of the weight of the urea phosphate, and the emulsifier accounts for 0.5% of the weight of the urea phosphate, and the stirring is continued at 100°C to obtain a colloid, the colloid is placed in an emulsifier for emulsification, and then transferred to a polymerization furnace for polymerization at 240°C and 10Kpa to obtain a composite material, and the composite material is cooled, dried, and crushed to obtain intermediate microspheres A, and the particle size of the intermediate microspheres A is 0.5μm;

[0084] S20: Mixing intermediate microspheres A and N-aminoethyl-3-aminopropyltriethoxysilane in a weight ratio of 1:1 in N,N-dimethylformamide and heating to 80°C, reacting for 10 hours under nitrogen protection, filtering, washing, and drying to obtain intermediate microspheres B with amino groups;

[0085] S30: para-acetoxystyrene, trioxymethylene and intermediate microspheres B in a weight ratio of 1:1:1 are mixed in methanol, 37% concentrated hydrochloric acid is slowly added dropwise, and the amount of concentrated hydrochloric acid added is 30% of the weight of the intermediate microspheres B, and then reacted at 50° C. under nitrogen protection for 12 hours, and the reaction solution is neutralized to neutrality with sodium bicarbonate, and filtered, washed, and dried to obtain intermediate microspheres C;

[0086] S40: The intermediate microspheres C with a weight ratio of 1:5 are placed in a solution of 3-mercaptopropyltriethoxysilane, and the solvent is a mixed solvent of ethanol and water with a volume ratio of 5:1. Then, AIBN accounting for 1% of the weight of the intermediate microspheres is added, and after reacting at 70°C under nitrogen protection for 5 hours, the modified expandable graphite 1# is obtained by suction filtration, washing and drying.

[0087] Modified expandable graphite 2#

[0088] The preparation method of the modified expandable graphite 2# comprises the following steps:

[0089] S10: Phosphoric acid and urea are mixed at a molar ratio of 1:1, and reacted at 80°C to obtain urea phosphate, expandable graphite, dispersant, and emulsifier are added to the urea phosphate, wherein the expandable graphite accounts for 30% of the weight of the urea phosphate, the dispersant accounts for 0.5% of the weight of the urea phosphate, and the emulsifier accounts for 0.5% of the weight of the urea phosphate, and the stirring is continued at 80°C to obtain a colloid, the colloid is placed in an emulsifier for emulsification, and then transferred to a polymerization furnace for polymerization at 150°C and 45Kpa to obtain a composite material, and the composite material is cooled, dried, and crushed to obtain intermediate microspheres A, and the particle size of the intermediate microspheres A is 10μm;

[0090] S20: Mix the intermediate microsphere A and N-aminoethyl-3-aminopropyltriethoxysilane in a weight ratio of 1:2 in N,N-dimethylformamide and heat to 80°C. React for 8 hours under nitrogen protection. Filter, wash and dry to obtain the intermediate microsphere B with amino groups. The reaction equation is as follows:

[0091]

[0092] S30: Monomer A, trioxymethylene and intermediate microspheres B in a weight ratio of 2:3:1 are mixed in methanol, 37% concentrated hydrochloric acid is slowly added dropwise, and the amount of concentrated hydrochloric acid added is 30% of the weight of the intermediate microspheres B. Then, the reaction is carried out at 60°C under nitrogen protection for 8 hours, and the reaction solution is neutralized to neutrality with sodium bicarbonate, filtered, washed and dried to obtain intermediate microspheres C. Monomer A is selected from diacetone acrylamide and benzylidene acetone in a molar ratio of 3:1, and the reaction equation is as follows:

[0093]

[0094] Wherein R represents monomer A, and both amino groups in the intermediate microsphere B in this step can participate in the reaction, thereby obtaining two compounds of the structure of Formula 1 and the structure of Formula 2, and the compound of the structure of Formula 1 accounts for more than 70% in the above reaction;

[0095] S40: placing the intermediate microspheres C with a weight ratio of 1:10 in a solution of 3-mercaptopropyltriethoxysilane, wherein the solvent is a mixed solvent of ethanol and water with a volume ratio of 5:1, and then adding AIBN accounting for 1% of the weight of the intermediate microspheres. After reacting at 60°C under nitrogen protection for 8 hours, filtering, washing and drying are performed to obtain modified expandable graphite 2#. In this step, the carbon-carbon double bond in the monomer A undergoes an addition reaction with 3-mercaptopropyltriethoxysilane.

[0096] Modified expandable graphite 3#

[0097] The difference between the modified expandable graphite 3# and the modified expandable graphite 2# is that in step S10, the expandable graphite accounts for 40% of the weight of the urea phosphate, and the remaining steps are the same as those of the modified expandable graphite 2#.

[0098] Modified expandable graphite 4#

[0099] The difference between the modified expandable graphite 4# and the modified expandable graphite 2# is that in step S20, the weight ratio of the intermediate microspheres A and N-aminoethyl-3-aminopropyltriethoxysilane is 1:0.5, and the remaining steps are the same as those of the modified expandable graphite 2#.

[0100] Modified expandable graphite 5#

[0101] The difference between the modified expandable graphite 5# and the modified expandable graphite 2# is that the weight ratio of the monomer A, the formaldehyde compound and the intermediate microspheres B in step S30 is 0.8:3:1, and the remaining steps are the same as those of the modified expandable graphite 2#.

[0102] Modified expandable graphite 6#

[0103] The difference between the modified expandable graphite 6# and the modified expandable graphite 2# is that in step S30, the monomer A is selected from diacetone acrylamide and benzyl acetone in a molar ratio of 1:3, and the remaining steps are the same as those of the modified expandable graphite 2#.

[0104] Modified expandable graphite 7#

[0105] The difference between the modified expandable graphite 7# and the modified expandable graphite 2# is that in step S40, the weight ratio of the intermediate microspheres C to 3-mercaptopropyltriethoxysilane is 1:3, and the remaining steps are the same as those of the modified expandable graphite 2#.

[0106] Modified expandable graphite 8#

[0107] The difference between the modified expandable graphite 8# and the modified expandable graphite 2# is that the particle size of the intermediate microsphere A is 15 μm, and the remaining steps are the same as those of the modified expandable graphite 2#.

[0108] Comparison of modified expandable graphite D1#

[0109] The difference between the comparative modified expandable graphite D1# and the modified expandable graphite 2# is that step S10 is not performed, and in step S20, the expandable graphite with a weight ratio of 1:2 is directly reacted with N-aminoethyl-3-aminopropyltriethoxysilane, the particle size of the expandable graphite is 10 μm, and the remaining steps are the same as those of the modified expandable graphite 2#.

[0110] Comparison of modified expandable graphite D2#

[0111] The difference between the comparative modified expandable graphite D2# and the modified expandable graphite 2# is that steps S20-S40 are not performed, the intermediate microspheres A are the final modified expandable graphite, and the remaining steps are the same as those of the modified expandable graphite 2#.

[0112] Comparison of modified expandable graphite D3#

[0113] The difference between the comparative modified expandable graphite D3# and the modified expandable graphite 2# is that step S40 is not performed, the intermediate microspheres C are the final modified expandable graphite, and the remaining steps are the same as those of the modified expandable graphite 2#.

[0114] Comparison of modified expandable graphite D4#

[0115] The difference between the comparative modified expandable graphite D4# and the modified expandable graphite 2# is that 3-aminopropyltriethoxysilane is used instead of N-aminoethyl-3-aminopropyltriethoxysilane in step S20, and the remaining steps are the same as those of the modified expandable graphite 2#.

[0116] Test Example 1

[0117] The modified expandable graphite prepared above was subjected to a gas adsorption test. The test results are shown in Table 1. The test method is as follows:

[0118] Experimental group: 1g of modified expandable graphite was placed in the non-combustible plate of the reactor, and a polyurethane sheet (5cm long * 5cm wide * 1cm thick) without adding flame retardant was fixed and hung in the reactor. Oxygen (100ml / min) was introduced into the reactor, and the polyurethane sheet was ignited and burned with an ignition device until it was completely burned. The concentrations of HCN, CO2, CO, NO, and NO2 in the reactor were tested.

[0119] Blank group: A polyurethane sheet of the same material and size was fixed and hung in the reactor. Nothing was placed in the non-combustible sheet. After the combustion was completed, the concentrations of HCN, CO2, CO, NO, and NO2 in the reactor were recorded.

[0120] The polyurethane sheets of the experimental group and the blank group were prepared by placing polyether polyol, foam leveler, catalyst, blowing agent and water in a weight ratio of 75:2.7:1.5:1.5:1 in a container, mixing and stirring with a high-speed stirrer for 2 minutes to obtain a uniform mixed liquid, and then adding PAPI and stirring at a high speed for 20 seconds to obtain a mixture. The weight ratio of PAPI to water was 100:1. The mixture was quickly added to the mold for foaming, and the closed mold temperature was controlled at 65°C for 30 minutes for aging. After the foaming was completed, the mold was opened and cut into 5 cm long * 5 cm wide * 1 cm thick pieces.

[0121] The modified expandable graphite prepared in Example 1 was subjected to experimental group tests in turn, and the adsorption rates of various gases were calculated based on the comparison of the tested gas concentrations with the blank group. The calculation method is as follows:

[0122] HCN adsorption rate = (HCN concentration in blank group - HCN concentration in experimental group) / HCN concentration in blank group * 100;

[0123] CO2 adsorption rate = (CO2 concentration of blank group - CO2 concentration of experimental group) / CO2 concentration of blank group * 100;

[0124] CO adsorption rate = (CO concentration of blank group - CO concentration of experimental group) / CO concentration of blank group * 100;

[0125] NO adsorption rate = (NO concentration in blank group - NO concentration in experimental group) / NO concentration in blank group * 100;

[0126] NO2 adsorption rate = (NO2 concentration in blank group - NO2 concentration in experimental group) / NO2 concentration in blank group * 100.

[0127] Table 1

[0128]

[0129] According to the data in Table 1, the modified expandable graphite can adsorb HCN, CO2, CO, NO, and NO2. Therefore, when it is used in polyurethane sheets, it can adsorb and block the toxic gases produced in the early stage of combustion and reduce the combustion hazards.

[0130] Example 2

[0131] The present embodiment relates to a high-efficiency flame-retardant polyurethane and a preparation method thereof. The high-efficiency flame-retardant polyurethane comprises, by weight: 20-25 parts of microencapsulated dimethyl methylphosphonate, 100-130 parts of modified expandable graphite, 40-50 parts of polyether polyol, 30-50 parts of polyester polyol, 10-13 parts of chain extender, 130-150 parts of diisocyanate, 1-2 parts of foaming agent, 0.5-1 part of catalyst, 2-3 parts of surfactant and 1-2 parts of water.

[0132] The preparation method of the high-efficiency flame-retardant polyurethane comprises the following steps:

[0133] (1) mixing microencapsulated dimethyl methylphosphonate, modified expandable graphite, polyether polyol, polyester polyol, foaming agent, catalyst, surfactant and water to obtain a mixed solution;

[0134] (2) Adding a chain extender and diisocyanate to the mixed solution, stirring, and pouring into a mold for foaming and aging to obtain a highly efficient flame-retardant polyurethane material.

[0135] Polyurethanes 1#-8# and comparative polyurethanes D1#-D2# were prepared according to the above preparation method. The specific preparation method is as follows:

[0136] Polyurethane 1#

[0137] Preparation of microencapsulated dimethyl methylphosphonate:

[0138] S1: Disperse dimethyl methylphosphonate in water, stir at 25°C for 3h, then add 5% Tween 80 by weight of dimethyl methylphosphonate to start emulsification, the emulsification time is 120min, finally add dicyclohexylmethane diisocyanate dropwise, the weight ratio of dicyclohexylmethane diisocyanate to dimethyl methylphosphonate is 8:1, the weight ratio of dicyclohexylmethane diisocyanate to water is 1:1, and react at a constant temperature of 80°C for 2h to obtain an intermediate solution;

[0139] S2: Mix melamine, 37% formaldehyde aqueous solution and deionized water in a weight ratio of 1:2:8, and a weight ratio of melamine to dimethyl methylphosphonate of 0.5:1, adjust the pH to 8 with triethanolamine, and then stir at 50° C. to form a transparent liquid, and then add distilled water accounting for 15% of the weight of the deionized water to obtain a melamine-formaldehyde prepolymer solution;

[0140] S3: Add melamine-formaldehyde prepolymer solution to the intermediate solution, react at 60° C. for 3 hours, and obtain microencapsulated dimethyl methylphosphonate after filtration, washing and drying.

[0141] Preparation of chain extender:

[0142] S1: N, N-bis (hydroxymethyl) -urea was dissolved in a mixed solvent of water and ethanol in a weight ratio of 2: 1, and 85% formic acid solution and 37% formaldehyde solution were added at room temperature, and the molar ratio of N, N-bis (hydroxymethyl) -urea, formaldehyde and formaldehyde was 1: 1: 1, and then the temperature was raised to 80 ° C for 9 hours, and then the pH was adjusted to 10 with 10% NaOH solution, and the intermediate was obtained after ether extraction and drying;

[0143] S2: The intermediate was dissolved in ethanol, 2% of citric acid and 5% of disodium ethylenediaminetetraacetate by weight of N,N-bis(hydroxymethyl)urea were added, the temperature was raised to 60°C, 30% hydrogen peroxide was added, the molar ratio of hydrogen peroxide to N,N-bis(hydroxymethyl)urea was 1:1, the reaction was continued for 6 hours, the product was distilled and purified by silica gel column chromatography (the eluent was ethyl acetate: petroleum ether = 1:10) to obtain a chain extender.

[0144] Preparation of modified expandable graphite:

[0145] Expandable graphite with a particle size of 0.5 μm was placed in a vinyl tri(β-methoxyethoxy) silane solution, the weight ratio of expandable graphite to vinyl tri(β-methoxyethoxy) silane was 10:1, stirred at 60° C. for 3 h, then centrifuged and dried to obtain modified expandable graphite.

[0146] The preparation of polyurethane 1# includes the following steps:

[0147] (1) 20 parts of microencapsulated dimethyl methylphosphonate, 130 parts of modified expandable graphite, 50 parts of polyether triol (hydroxyl value of 350 mg KOH / g), 50 parts of polycaprolactone polyol (hydroxyl value of 650 mg KOH / g), 1 part of n-pentane, 0.5 parts of dibutyltin dilaurate, 2 parts of benzyl silicone oil and 1 part of water were mixed for 2 minutes to obtain a mixed solution;

[0148] (2) Add 10 parts of chain extender and 130 parts of dicyclohexylmethane diisocyanate to the mixed solution, stir for 20 seconds, pour into a mold, foam and mature at 80° C., and obtain polyurethane 1#.

[0149] Polyurethane 2#

[0150] Preparation of microencapsulated dimethyl methylphosphonate:

[0151] S1: Disperse dimethyl methylphosphonate in water, stir at 60°C for 2h, then add 5% of the weight of Span 80 to start emulsification, the emulsification time is 10min, and finally add toluene diisocyanate dropwise, the weight ratio of toluene diisocyanate to dimethyl methylphosphonate is 4:1, the weight ratio of toluene diisocyanate to water is 1:2, and react at a constant temperature of 10°C for 24h to obtain an intermediate solution;

[0152] S2: Mix melamine, 37% formaldehyde aqueous solution and deionized water in a weight ratio of 1:3:10, and a weight ratio of melamine to dimethyl methylphosphonate of 0.7:1, adjust the pH to 9 with triethanolamine, and then stir at 80° C. to form a transparent liquid, and then add distilled water accounting for 15% of the weight of the deionized water to obtain a melamine-formaldehyde prepolymer solution;

[0153] S3: Add melamine-formaldehyde prepolymer solution to the intermediate solution, react at 80° C. for 2 h, and obtain microencapsulated dimethyl methylphosphonate after filtration, washing and drying.

[0154] Preparation of chain extender:

[0155] S1: N, N-bis (hydroxymethyl) -urea was dissolved in a mixed solvent of water and ethanol in a weight ratio of 3:1, and 85% formic acid solution and 37% formaldehyde solution were added at room temperature, and the molar ratio of N, N-bis (hydroxymethyl) -urea, formaldehyde and formaldehyde was 1:1:1, and then the temperature was raised to 70 ° C for 12 hours, and then the pH was adjusted to 11 with 10% NaOH solution, and the intermediate was obtained after ether extraction and drying;

[0156] S2: The intermediate was dissolved in ethanol, 2% of citric acid and 5% of disodium ethylenediaminetetraacetate by weight of N,N-bis(hydroxymethyl)urea were added, the temperature was raised to 70°C, 30% hydrogen peroxide was added, the molar ratio of hydrogen peroxide to N,N-bis(hydroxymethyl)urea was 1:1, the reaction was continued for 4 hours, the product was distilled and purified by silica gel column chromatography (the eluent was ethyl acetate: petroleum ether = 1:10) to obtain a chain extender.

[0157] Preparation of modified expandable graphite:

[0158] Expandable graphite with a particle size of 10 μm was placed in a triisostearoyl titanate isopropyl ester solution, the weight ratio of expandable graphite to triisostearoyl titanate is 10:1, stirred at 60° C. for 3 h, then centrifuged and dried to obtain modified expandable graphite.

[0159] Preparation of polyurethane 2#:

[0160] (1) 25 parts of microencapsulated dimethyl methylphosphonate, 100 parts of modified expandable graphite, 70 parts of polyether tetraol (hydroxyl value of 450 mg KOH / g), 80 parts of polycarbonate polyol (hydroxyl value of 350 mg KOH / g), 2 parts of n-hexane, 1 part of dibutyltin dilaurate, 3 parts of methyl hydrogen silicone oil and 2 parts of water were mixed for 2 minutes to obtain a mixed solution;

[0161] (2) Add 13 parts of chain extender and 150 parts of toluene diisocyanate to the mixed solution, stir for 20 seconds, pour into a mold, foam and mature at 65° C., and obtain polyurethane 2#.

[0162] Polyurethane 3#

[0163] The difference between polyurethane 3# and polyurethane 2# is that in the step S1 of preparing microencapsulated dimethyl methylphosphonate, polyvinyl alcohol, polyvinyl pyrrolidone and distilled water in a weight ratio of 1:1:240 are mixed to form an aqueous phase; styrene, divinylbenzene, dimethyl methylphosphonate and azobisisobutyronitrile in a weight ratio of 27:3:30:0.7 are dissolved to form an oil phase. When the system temperature is 50°C, the oil phase is added to the aqueous phase in a weight ratio of 1:1 between the aqueous phase and the oil phase, emulsified for 5 minutes at a stirring rate of 1000rpm, and the pH of the system is adjusted to 4.5 with acetic acid to obtain an intermediate solution. The remaining steps S2-S3 are the same as polyurethane 2#, and the preparation of the chain extender, modified expandable graphite and polyurethane are the same as polyurethane 2#, so as to obtain polyurethane 3#.

[0164] Polyurethane 4#

[0165] The difference between the polyurethane 3# and the polyurethane 2# is that 1,4-butanediol is used as the diol, and the rest is the same as the polyurethane 2#, that is, the polyurethane 3# is obtained.

[0166] Polyurethane 5#

[0167] The difference between the polyurethane 5# and the polyurethane 2# is that N,N-bis(hydroxymethyl)-urea is used as the diol, and the rest is the same as the polyurethane 2#, that is, the polyurethane 5# is obtained.

[0168] Polyurethane 6#

[0169] The difference between the polyurethane 6# and the polyurethane 2# is that the modified expandable graphite 2# of Example 1 is used as the modified expandable graphite, and the rest is the same as the polyurethane 2#, so as to obtain the polyurethane 6#.

[0170] Polyurethane 7#

[0171] The difference between the polyurethane 7# and the polyurethane 2# is that the comparative modified expandable graphite D1# of Example 1 is used as the modified expandable graphite, and the rest is the same as the polyurethane 2#, that is, the polyurethane 7# is obtained.

[0172] Polyurethane 8#

[0173] The difference between the polyurethane 8# and the polyurethane 2# is that the comparative modified expandable graphite D2# of Example 1 is used as the modified expandable graphite, and the rest is the same as the polyurethane 2#, so as to obtain the polyurethane 8#.

[0174] Comparison with polyurethane D1#

[0175] The difference between the comparative polyurethane D1# and the polyurethane 2# is that dimethyl methylphosphonate is directly used as the flame retardant, and the rest is the same as the polyurethane 2#, that is, the comparative polyurethane D1# is obtained.

[0176] Comparison of polyurethane D2#

[0177] The difference between the comparative polyurethane D2# and polyurethane 2# is that no modified expandable graphite is added, and the rest is the same as polyurethane 2#, that is, comparative polyurethane D2#.

[0178] Test Example 2

[0179] The density, thermal conductivity, flame retardancy and mechanical properties of the polyurethane prepared in Example 2 above were tested. The results are shown in Table 2 below.

[0180] Table 2

[0181]

[0182] Test Example 3

[0183] The polyurethane prepared in Example 2 was placed at 60° C. and 50% humidity for 30 days, and then the oxygen index of the polyurethane was tested. The test results are shown in Table 3 below.

[0184] Table 3

[0185]

[0186]

[0187] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A highly efficient flame-retardant polyurethane, characterized in that: The invention comprises, by weight: 20-25 parts of microencapsulated dimethyl methylphosphonate, 100-130 parts of modified expandable graphite, 50-70 parts of polyether polyol, 50-80 parts of polyester polyol, 10-13 parts of chain extender, 130-150 parts of diisocyanate, 1-2 parts of foaming agent, 0.5-1 parts of catalyst, 2-3 parts of surfactant and 1-2 parts of water; The microencapsulated dimethyl methylphosphonate comprises a capsule core, a first capsule wall and a second capsule wall from the inside to the outside, wherein the capsule core is dimethyl methylphosphonate, the first capsule wall is polyurethane, and the second capsule wall is melamine-formaldehyde copolymer; The modification method of the modified expandable graphite is: S10: Phosphoric acid and urea are mixed at a molar ratio of (0.5-1):1, and reacted at 80-100°C to obtain urea phosphate, expandable graphite, a dispersant, and an emulsifier are added to the urea phosphate, and the mixture is stirred at 80-100°C to obtain a colloid, the colloid is emulsified in an emulsifier, and then transferred to a polymerization furnace to polymerize at 150-240°C and 10-45Kpa to obtain a composite material, and the composite material is cooled, dried, and crushed to obtain intermediate microspheres A; S20: mixing the intermediate microsphere A and N-aminoethyl-3-aminopropyltriethoxysilane in a solvent and heating to 80° C. to react, filtering, washing, and drying to obtain the intermediate microsphere B with amino groups; S30: reacting monomer A, formaldehyde compound and intermediate microsphere B under an acid catalyst, filtering, washing and drying to obtain intermediate microsphere C, wherein monomer A is selected from at least one of p-acetoxystyrene, diacetone acrylamide and benzylidene acetone; S40: placing the intermediate microspheres C in a 3-mercaptopropyltriethoxysilane solution, reacting under the initiator, filtering, washing and drying to obtain modified expandable graphite.

2. The high-efficiency flame-retardant polyurethane according to claim 1, characterized in that: The preparation method of the microencapsulated dimethyl methylphosphonate is: S1: Disperse dimethyl methylphosphonate in water, stir at 25-60°C for 2-3h, then add emulsifier to start emulsification for 10-120min, finally add diisocyanate dropwise, and react at a constant temperature of 10-80°C for 2-24h to obtain an intermediate solution; S2: Mix melamine, formaldehyde aqueous solution and deionized water in a weight ratio of 1: (2-3): (8-10), adjust the pH to 8-9 with triethanolamine, and then stir at 50-80°C to form a transparent liquid, and then add a certain amount of distilled water to obtain a melamine-formaldehyde prepolymer solution; S3: adding melamine-formaldehyde prepolymer solution to the intermediate solution, reacting at 60-80° C. for 2-3 hours, filtering, washing and drying to obtain microencapsulated dimethyl methylphosphonate.

3. The high-efficiency flame-retardant polyurethane according to claim 2, characterized in that: In step S1, the weight ratio of the diisocyanate to dimethyl methylphosphonate is at least one of 4:1, 6:1, and 8:1, and the weight ratio of the diisocyanate to water is 1:1-2.

4. The high-efficiency flame-retardant polyurethane according to claim 2, characterized in that: In step S3, the weight ratio of the intermediate solution to the melamine-formaldehyde prepolymer solution is 1:(1.5-2).

5. The high-efficiency flame-retardant polyurethane according to claim 1, characterized in that: The chain extender is prepared from N,N-bis(hydroxymethyl)-urea, and the specific preparation method is as follows: S1: dissolving N,N-bis(hydroxymethyl)-urea in a solvent, adding formic acid and formaldehyde at room temperature, wherein the molar ratio of N,N-bis(hydroxymethyl)-urea, formic acid and formaldehyde is 1:1:1, then heating to 70-80°C for reaction for 9-12h, then adjusting the pH to 10-11, extracting and drying to obtain an intermediate; S2: dissolving the intermediate in ethanol, adding a small amount of citric acid and disodium ethylenediaminetetraacetate, heating to 60-70°C, adding hydrogen peroxide, wherein the molar ratio of hydrogen peroxide to N,N-bis(hydroxymethyl)-urea is 1:1, reacting for at least 4 hours, distilling and purifying to obtain the chain extender.

6. The high-efficiency flame-retardant polyurethane according to claim 5, characterized in that: The added amount of the citric acid accounts for 2% of the weight of N,N-bis(hydroxymethyl)-urea, and the added amount of the disodium ethylenediaminetetraacetate accounts for 5% of the weight of N,N-bis(hydroxymethyl)-urea.

7. The high-efficiency flame-retardant polyurethane according to claim 1, characterized in that: The diisocyanate is selected from at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and hexamethylene diisocyanate; The polyether polyol is selected from polyether triol or polyether tetraol, and the hydroxyl value of the polyether polyol is 350-650 mg KOH / g; The polyester polyol is selected from at least one of polycaprolactone polyol, polycarbonate polyol and polyacrylate polyol, and the hydroxyl value of the polyester polyol is 350-650 mg KOH / g.

8. The high-efficiency flame-retardant polyurethane according to claim 1, characterized in that: The foaming agent is selected from at least one of n-pentane, n-hexane and cyclohexane; The catalyst is selected from at least one of dibutyltin dilaurate, bis(dimethylaminoethyl) ether, N,N-dimethylcyclohexylamine, and 1,4-dimethylpiperazine; The surfactant is selected from at least one of benzyl silicone oil, diethyl silicone oil, methyl hydrogen silicone oil and methyl vinyl silicone oil.

9. The method for preparing the high-efficiency flame-retardant polyurethane according to any one of claims 1 to 8, characterized in that: The steps include: (1) mixing microencapsulated dimethyl methylphosphonate, modified expandable graphite, polyether polyol, polyester polyol, foaming agent, catalyst, surfactant and water to obtain a mixed solution; (2) Adding a chain extender and diisocyanate to the mixed solution, stirring the mixed solution, pouring the mixture into a mold for foaming and aging, and obtaining a highly efficient flame-retardant polyurethane material.

Citation Information

Patent Citations

  • Efficient halogen-free anti-inflaming polyurethane hard foam and preparation method thereof

    CN101724254A

  • Flame-retardant phase change energy storage microcapsule and preparation method thereof

    CN113058513A